Optimization of Investment Resource Allocation In Enterprises of Water Supply and Sewerage Sector - Elina Moroz (Communications of International Proceedings, 2025)
The article presents possible options for the allocation of planned investment resources for a water supply and sewerage enterprise in Ukraine, taking into account socio-ecological development factors. The article outlines selected options for the distribution of investment resources and analyzes the expected outcomes of investing exclusively in economic measures versus socio-ecological initiatives. The conducted research revealed that the greatest synergistic effect for the studied enterprise can be achieved by combining investment in both economic and socio-ecological approaches.
Keywords: optimization; sustainable development; enterprises of water supply and sewerage sector; investment resource